Revitalizing Islamic Education Through STEAM to Achieve the SDGS: A Pathway to Higher-Order Thinking and Academic Excellence - Annas Fajar Rohmani; Wachidi; Waston; Abdunrorma Samaalee; Camila Garcia (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to examine the effectiveness of integrating the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach into Islamic Religious Education (IRE) to enhance students’ higher-order thinking skills (HOTS) and academic performance, while promoting value-based character development. Theoretical framework: The study is grounded in Bloom’s Taxonomy, focusing on cognitive levels C3 (application), C4 (analysis), and C5 (evaluation), combined with Islamic epistemology and constructivist learning theory, which emphasize holistic and contextual knowledge. Literature review: Existing literature highlights the success of STEAM in scientific disciplines, but its application in religious education remains limited. Classical Islamic scholars advocated the integration of rational, empirical, and spiritual knowledge. Embedding STEAM in IRE aligns with this legacy and supports Sustainable Development Goal 4.7, promoting inclusive, ethical, and future-ready education. Methods: Using a quasi-experimental pretest-posttest control group design, this study involved eighth-grade students at SMP Negeri 13 Surakarta. The experimental group received STEAM-based instruction on muamalah (Islamic economic ethics), while the control group followed traditional methods. Quantitative data were analyzed using t-tests; qualitative insights were drawn from student journals and reflections. Results: Students in the STEAM group showed significant improvements in HOTS, with mastery levels reaching 96%, alongside notable academic gains and deeper engagement. Implications: Integrating STEAM into IRE fosters critical, creative, and ethically grounded learners. It offers a transformative model for modern Islamic education that bridges tradition and innovation. Novelty: This study pioneers an interdisciplinary framework merging STEAM with Islamic values, providing empirical support for its relevance in 21st-century education.